LAW AND TRUST IN POLICE: An Interrogation Study in a Forensic Linguistic Perspective - Sri Waljinah; Kelik Wardiono; Natangsa Surbakti; Purwadi Wahyu Anggoro (Jurnal Ilmiah Advokasi, 2024)
Citizens' rights in the legal field are to obtain justice when dealing with legal cases which in the handling process involve investigators and examinees. The problem in this research is that the interrogation process is less humane in its implementation in the Police. The aim of this research is to describe the interrogation process in the Police from a forensic linguistic perspective and examine the laws and regulations regarding interrogation and its implementation in the Police. The approach method is normative juridical and qualitative descriptive type. The data collection method uses library research on primary and secondary data sources using recording and note-taking techniques. Data analysis uses qualitative analysis methods with logical thinking based on the logic of analogical induction or deductive interpretation. Data validation uses triangulation techniques based on several data sources to compare one data source with another data source. The results of the research are: (1) the interrogation process in the Police from a forensic linguistics perspective, namely humanist and less humanist, and (2) the interrogation process in the Police is generally running in accordance with statutory regulations but there are still violations in its implementation.Keywords: Law, interrogation, forensic linguistics